Integrating Low Cost IMU With Building Heading In Indoor Pedestrian Navigation - Khairi Abdul Rahim; Chris Hide; Terry Moore; Chris Hill (SpringerOpen, 2024)
Journal of Global Positioning Systems (2011) Vol.10, No.1 :30-38